The Use of Special Knowledge in View of Investigation of the Crimes of an Extremist Nature - SHIDEMOV, Azamat Garifullaevich (Journal of Advanced Research in Law and Economics; Vol 8 No 2 (2017): Volume VII, Issue 2(24), Spring 2017, 2017)
The main purpose of this research is the study of the institution of special knowledge within the framework of modern methodological approaches based on the investigative practices, and the features of the appointment of forensic inquiry as a form of involvement of the special knowledge in the detection and investigation of the crimes of an extremist nature. The extensive data from the general theory, logic, psychology, the cycle of criminal procedural sciences as well as criminalistics and forensics are used in this study. The legal sources of the study are: the laws and regulations, the departmental regulations of the Ministry of Internal Affairs of the Republic of Kazakhstan, the Ministry of Justice of the Republic of Kazakhstan, the Decrees of the Government of the Republic of Kazakhstan regulating the execution of criminalistic and forensic inquiries of various types. The awareness of an investigator in the field of use of special knowledge opens up the opportunities for the establishment of the reasons, which had contributed to the commission of the crimes of an extremist nature. The proposals, conclusions and recommendations offered can be used in the development of the general theory of criminology and criminal proceedings, as well as to solution on a theoretical level of the problems related to the methods of investigation of the crimes of an extremist nature, associated with the need to use the special knowledge. The proposals offered and the results of the study can be used in the process of improvement of the expert, investigative and judicial practice, as well as in the educational process (‘Criminal Procedure’, ‘Criminalistics’).